Printed Transparent Thin Film Zn-MnO2 Battery - Lao-atiman, Woranunt; Julaphatachote, Thanatham; Boonmongkolras, Passarut; Kheawhom, Soorathep (Journal of the Electrochemical Society, 2017)
In this work, transparent thin film zinc-manganese dioxide (Zn-MnO2) batteries were fabricated using an inexpensive screen-printing technique. Both electrodes were fabricated as micro-electrode arrays with feature size of 50 μm, which are below resolution of human eyes. Thus, the electrodes appeared transparent. Moreover, a transparent alkaline polymer gel electrolyte (PGE) film prepared by polymerization of acrylate, potassium hydroxide and water was used as a quasi-solid-state electrolyte. The PGE film functioned as both an electrolyte and an insulator/separator. Three patterns of the micro-electrodes with different percentages of opening area (75%, 80% and 85%) were investigated. The open-circuit voltages of the batteries fabricated were 1.25 V. Ohmic loss zones were 0.1-2.0 mA.cm− 2. The battery with an opening area of 80% provided an average transparency of 90% without significantly affecting battery performance. Moreover, energy density of the battery could be further increased by increasing the thickness of the electrodes. By increasing the thickness of the micro-electrodes upto 80 μm, energy density of the battery was significantly enhanced without loosing its transparency.